The Effect between Low-Intensity Resistance Training and Maximum Fat Oxidation Intensity Aerobic Exercise on Body Composition of Young Obese Women - Sun, Shishun; Xu, Xiongzhuang; Peng, Li (Quality in Sport, 2025)
Objectives: Through comparative study on the effect between low-intensity resistance training (RT) and maximum fat oxidation intensity aerobic exercise（FATmax AE）on body composition of young obese women to explore the effect of RT on fat loss. Methods: Thirty-four young obese women with body fat percentages (BF %) of 30% or more were randomly assigned to FATmax AE group (AEG, control group) and low-intensity resistance training group (RTG, experimental group). The subjects in two groups completed 3*45 min/wk of FATmax AE or RT of 15 maximum repetitions (RM) respectively for 12 weeks. Height, weight, waist and hip circumference (then BMI and WHR were calculated), body fat percentage (BF %), fat mass (FM), muscle mass (MM) were measured at pre-, mid- and post- intervention. Results: Body weight, BMI, WHR, BF% and FM decreased, and MM increased significantly (all p<0.05) in both groups after 12 week of intervention. A greater decrease of body weight and BMI and more MM growth in RTG than those in AEG was found (all p<0.05). Conclusions: Low-intensity RT has the same effect as FATmax AE in reducing BF% and FM in young obese women in 12 weeks of exercise training (3*45 min/wk). Take into account its longer term effects of fat loss due to more MM growth, low-intensity RT should be recommended as one of the fat-loss activities.